COMPARISON OF THE ACADEMIC PERSPECTIVES OF ACCOUNTING FACULTY MEMBERS IN UNIVERSITIES OF TURKEY AND AROUND THE WORLD - Gül, Meltem; Aksu, İbrahim (My University, 2021)
The main objective of this study is to examine the profiles of accounting faculty members in the top 100 universities of the world which are ranked and published in the business management program by Quacquarelli Symonds QS organization, in terms of variables such as gender, title (rank), number of publications and citations; and to compare them with the profiles of accounting faculty members in Turkey. In order to make this comparison, universities in Turkey were divided into 4 groups: the oldest universities in Turkey, the best universities, foundation universities and newly established universities, and 10 universities were selected from each group. Thus, the closest and furthest groups to the faculty member profile in the best universities in the world would be identified and the general profile of the faculty members in Turkey would be revealed. One result to the study reveals that the average number of accounting faculty members in the best universities around the world and the number of academic studies and citations of these academicians constitute a larger number compared to Turkey
Keywords: Faculty member profile; education of accounting; universities in Turkey